Preferencing, Internalization of Order Flow, and Tacit Collusion: Evidence from Experiments - Kluger, Brian D.; Wyatt, Steve B. (Journal of Financial and Quantitative Analysis, 2002)
Brian D. Kluger, Steve B. Wyatt, Preferencing, Internalization of Order Flow, and Tacit Collusion: Evidence from Experiments, The Journal of Financial and Quantitative Analysis, Vol. 37, No. 3 (Sep., 2002), pp. 449-469